The Use of Potassium Sorbate in Vacuum Packaged Savak Tulum Cheese - Demir, Pelin; Oksuztepe, Gulsum; Incili, G. Kursad; Ilhak, O. Irfan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2017)
This study was carried out to determine the shelf life of vacuum packaged Savak tulum cheese supplemented with potassium sorbate. For this purpose, ewe milk was divided to four groups as K (control group), A (added with 0.05% potassium sorbate), B (added with 0.1% potassium sorbate), and C (added with 0.2% potassium sorbate). The groups were stored in refrigerator (4 degrees C) and analyzed for microbiological (Total mesophilic aerobic bacteria, LLP, lactic streptococcus, coliforms, lipolytic bacteria, proteolytic bacteria, yeast and mold, E. coli, Staph. aureus, and C. perfringens), chemical (pH, acidity, aw, fat, salt, dry matter, ash, and residue sorbic acid) and sensorial (package, appearance, structure, odor, taste and general acceptability) attributes on days 0, 15, 30, 60, 90, 120, 150, 180, 210.and 240. of storage. The control group, A, B and C groups were deteriorated as regards sensorial on days 120, 150, 180. and 270. of storage, respectively. C. perfringens was found in none of the groups. E. coli was found to be below detection limit after 90 days in control group, 15 days in A and B groups, and on day 0 in C group. Staph. aureus wasfound to be below detection limit after 30 days in control group, 15 days in A and B groups, and on day 0 in C group. Residue sorbic acid level was detected as 0.002 ppm in group A on day 120, 0.006 ppm in group B on day 150, and 0.11 ppm in group Con day 240. The most popular group by panelists was group C. Consequently, it was seen that savak tulum cheese can be vacuum packaged and consumed in small porsions by consumers, and the use of potassium sorbate in vacuum packaged Savak tuulum cheese has an inhibitory effect on E. coli and Staph. aureus.
Vakum paketli şavak tulum peynirlerinde potasyum sorbatın kullanımı
Keywords: Vacuum package; Tulum cheese; Potassium sorbate